Geschichte und Geschichten Aesthetischer und historiographischer Diskurs bei N. M. Karamzin - Brinkjost, Ulrike (Slavistische Beitraege, 2000)
The focus of the following work is the Russian author N.M. Karamzin (1766-1826), who is still known in Russia today for his sentimentalist narrative "Bednaja Liza" and the twelve-volume "Istorija gosudarstva rossijskogo". At the end of the 18th and in the first third of the 19th century, at the time of their creation, his works were widely read, Karamzin, as a sentimentalist writer as well as a historiographer, had some success in the contemporary reading public. The work is chronological, beginning with Karamzin's early work, Pisma Russkogo putešestvennika (1791-92), then examining a selection of sentimentalist narratives that appeared in the period 1792-1803 and ending with Istorija gosudarstva rossijskogo ", whose first eight volumes were published in 1818. Examined are the different discourses, which are assigned to the text categories travel writing, sentimentalistische povest 'and historiography, and others. in terms of narrative linkage.